Copper‐mediated 1, 4‐Conjugate Addition of Boronic Acids and Indoles to Vinylidenebisphosphonate leading to gem‐Bisphosphonates as Potential Antiresorption Bone Drugs. Issue 9 (19th August 2014) - Chiminazzo, Andrea; Sperni, Laura; Damuzzo, Martina; Strukul, Giorgio; Scarso, Alessandro
Abstract A wide range of gem‐bisphosphonate tetraethyl esters as precursors for bisphosphonic acids, which are potent inhibitors of bone resorption, bearing alkyl, aryl, and indole substituents in the β position were prepared through the CuII‐catalyzed 1, 4‐conjugate addition of boronic acids and indoles to vinylidenebisphosphonate tetraethyl ester.